Physicochemical, in vitro digestibility and functional properties of carboxymethyl rice starch cross-linked with epichlorohydrin - Ornanong S. Kittipongpatana (2018)
Cross-linked carboxymethyl rice starches (CL-CMRSs) were prepared from reactions between native rice starch and varied concentrations (0.1-15% w/w, M-0.1 to M-15) of epichlorohydrin (ECH) in a simultaneous carboxymethylation- crosslinking reaction setup using methanol as the solvent. The degree of carboxymethyl substitution was between 0.24 and 0.28, while apparent amylose contents were lowered due to modification. SEM images showed minor change on the granule surface, while XRD profiles indicated slight loss of crystallinity. DSC thermograms revealed no transition peak in all treated samples. The water uptake (WU), swelling volume (SV) and free swelling capacity (FSC) of CL-CMRSs increased significantly as a result of the modification, while swelling of CMRSs cross-linked with 2% (M-2) and 3% (M-3) ECH yielded FSC values and WU values that were much greater than those of native starches and were comparable to that of Explotab®. All modified starch samples showed increased amount of rapidly digestible starch (RDS), while cross-linking with 5-7.5% ECH raised the resistant starch (RS) content, compared to native starch. M-2 also showed promising results in tablet disintegration test. ECH-CL-CMRSs could potentially be used as an excipient in pharmaceutical and food/food supplement products. © 2013 Elsevier Ltd.